Iran’s Nuclear Program: A Case Study of Mistrust, Hatred and Betrayal - Riaz A. Khokhar (CISS Insight Journal, 2021)
Few studies have examined the international community’s pursuit of stringent measures aimed at eliminating military dimension of Iran`s nuclear program. The purpose of this study is to examine the reasons behind the extensive and intrusive international measures against Iran’s nuclear program despite IAEA reports and intelligence assessments reporting that Iran does not have a nuclear weapons program. This study drew one major conclusion that there is insurmountable mistrust and hatred between Iran and the West originating from their historical interaction since the early 19th century that reached the zenith after the 1979 Iranian revolution. For the West, the source of mistrust, hatred, and betrayal was Iran’s hardline ideology against the West and secret illegal nuclear activities outside the IAEA safeguards. Iran’s feeling of betrayal and lack of trust in the major Western powers originated from the West’s breakup of promises, withdrawal from agreements, repeated attacks on Tehran’s nuclear facilities and scientists, and unending economic sanctions.